Analysis of the influence of intergenerational differences on cross-generational cooperation among nurses - Pawlak, Natalia; Serafin, Lena; Czarkowska-Pączek, Bożena (Nursing in the 21st Century, 2022)
ANALYSIS OF THE INFLUENCE OF INTERGENERATIONAL DIFFERENCES ON CROSS-GENERATIONAL COOPERATION AMONG NURSESIntroduction. The professional group of nurses is characterized by generational diversity. Representatives of diff erent age groups have similar attitudes and values shaped by the sociocultural environment. Understanding the differences between generations and building multi-generational teams help in providing nursing services of the highest level.Aim. The aim of the study was to analyze the infl uence of generational diff erences on intergenerational cooperation among nurses.Material and methods. A non-systematic review and analysis of published articles both in Polish and English.Discussion. Each generation has its own values and beliefs. Therefore, behavior and nursing practice may diff er among generations. There are many challenges in multi-generational work environments, e.g. team communication, confl icts, work-life balance, and the ability to learn from colleagues with regards to everyday nursing practice and the use of technology. The main intergenerational diff erentiation can be seen in attitudes to work and professional development, communication, leadership and management.Summary. Managing a team should involve identifi cation of the employees’ strengths, while addressing their weaknesses in certain skills. The support of mentors and development opportunities are crucial aspects of work for nurses at the beginning of their career.The eff ectiveness of team communication can be increased by encouraging open communication with respect for members of each generation. Promoting the exchange of knowledge and work experience in daily nursing practice will help each generation achieve its full potential, which will, in turn, enable the provision of both high quality patient care and employee satisfaction.